Determinants of Attainment of High Class of the Degree of University Students; In the Sri Lankan Context - Ruwandi Hathella (International Journal of Education, Teaching, and Social Sciences, 2022)
The academic performance of undergraduates in Sri Lanka is a noticeable aspect in the highereducation sector of the country. A high class in the degree is a common challenge for alluniversity students when talking about their academic phase. Therefore, the extant researchtries to identify the factors that affect the attainment of a high class in the degree of universitystudents in Sri Lanka. A high class is conclusively referred to as a first class degree and asecond class upper division degree. Data were collected from 148 fresh graduates of the year2021, through the convenience sampling method. The survey design was used and thus, astructured questionnaire was distributed in the form of Google forms to the graduates for datacollection. The Binary Logistic Regression was the statistical tool applied for the analysisprocess. Results of the study revealed that gender, A/L attempt to the university entrance,lecture attendance, time management, internet usage, and self-motivation were the significantdeterminants of achievement of a high class in the degree. The present study, therefore, broughtout recommendations to support undergraduates, university lecturers, and administration toenhance the academic performance of undergraduates for the attainment of high class in thedegree.